The importance of recognizing worthlessness for suicide prevention in adolescents with Attention-deficit/hyperactivity disorder - Katzenmajer-Pump, Luca; Komáromy, Dániel; Balázs, Judit (Frontiers in Psychiatry, 2022)
Background: Attention deficit hyperactivity disorder (ADHD) is one of the most common psychiatric diagnoses among children and adolescents. Depression and general anxiety disorder (GAD) are often co-occurring with ADHD among children and adolescents. Previous studies have found that ADHD, depression and GAD are all strongly correlated with suicidal thoughts and planning. Aim: The current study aimed to further explore the association between ADHD, GAD and depressive symptoms as well as their association with suicidal thoughts and planning among adolescents. Method: Adolescents with ADHD diagnosis were involved from child psychiatry outpatient clinics and adolescents without a psychiatric treatment or diagnosis were enrolled from high schools in Hungary. The Mini International Neuropsychiatric Interview for Children and Adolescents was used to evaluate psychiatric symptoms and disorders as well as suicidal thoughts and planning. Regularized psychological networks were used to investigate the associations. Results: Altogether 185 adolescents (58 females and 127 males; mean age 14.79 years, SD=1.48), 89 with ADHD and 96 without ADHD were enrolled. Depression symptom worthlessness was directly related to suicidal thoughts and planning, CI95 of the logit B between worthlessness and suicidal thought [0.72, 1.66]. Both ADHD and anxiety were indirectly related to suicidal thoughts and planning through depression: CI95 of the logit B between being disorganized and feeling worthless is [0.38, 3.02], and CI95 of the logit B between being distressed and feeling worthless is [0.57, 2.52]. Conclusions: This study draws the attention of clinicians to the importance of recognizing “worthlessness” for suicide prevention in adolescents with ADHD. Furthermore, the results support previous studies, whereby symptoms of depression and anxiety mediate the relationship between ADHD and suicidal thoughts and planning. These results highlight the importance of ADHD comorbidities with depression and GAD and their effect on suicidal thoughts and planning.